2008
DOI: 10.1175/2008jas2793.1
|View full text |Cite
|
Sign up to set email alerts
|

Interannual Variability and Trends of Extratropical Ozone. Part II: Southern Hemisphere

Abstract: A principal component analysis (PCA) is applied to the Southern Hemisphere (SH) total column ozone following the method established for analyzing the data in the Northern Hemisphere (NH) in a companion paper. The interannual variability (IAV) of extratropical O 3 in the SH is characterized by four main modes, which account for 75% of the total variance. The first two leading modes are approximately zonally symmetric and relate to the Southern Hemisphere annular mode and the quasi-biennial oscillation. The thir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 39 publications
1
13
0
Order By: Relevance
“…While ERA-40 total column ozone has been reported to agree well with independent observations [Dethof and Hólm, 2004;Jiang et al, 2008b], studies involving ERA-40 ozone profiles seem scarce. Comparing ERA-40 ozone to sonde observations at high latitude, we find that although the annual cycle is captured well, polar ozone variability is underestimated in this data set.…”
Section: Comparison To Era-40 Ozonementioning
confidence: 76%
“…While ERA-40 total column ozone has been reported to agree well with independent observations [Dethof and Hólm, 2004;Jiang et al, 2008b], studies involving ERA-40 ozone profiles seem scarce. Comparing ERA-40 ozone to sonde observations at high latitude, we find that although the annual cycle is captured well, polar ozone variability is underestimated in this data set.…”
Section: Comparison To Era-40 Ozonementioning
confidence: 76%
“…In this paper we include several dynamical proxies in the statistical regression model that help to capture the interannual ozone variability observed in the upper and middle stratosphere over Syowa station. The attribution of ozone variability described in this paper is specific to the processes affecting ozone at the Antarctic coastal area, and may be different for other geolocations above the Antarctic continent because the polar vortex exhibits nonzonal features during the austral spring time (Schoeberl et al, 1992;Manney et al, 1995Manney et al, , 1999Jiang et al, 2008;Hitchman and Rogal, 2010;Hassler et al, 2011;and references therein).…”
Section: Trend Evaluationmentioning
confidence: 94%
“…Variations in the Brewer-Dobson circulation (BDC), in wave activity, and in the polar vortex all contribute to the observed distribution of ozone (e.g., Manney et al, 1995;Jiang et al, 2008;Hitchman and Rogal, 2010). Conversely, ozone depletion has been shown to affect the circulation in the Antarctic's stratosphere and troposphere (e.g., Thompson and Solomon, 2002;Li et al, 2010;Oman et al, 2010, Son et al, 2010.…”
Section: Proxy Data Setsmentioning
confidence: 99%
“…Some recent studies further suggest that atmospheric processes have significant influences on the temporal variability of CO 2 Jiang et al 2010;Wang et al 2011;Jiang et al 2013Jiang et al , 2012. It was found that the intraseasonal variability (e.g., MaddenJulian oscillation and semiannual oscillation) influence CO 2 concentrations in the middle troposphere Jiang et al 2013). Interannual variability (e.g., El…”
Section: Introductionmentioning
confidence: 99%
“…Niño-Southern Oscillation) can also modulate CO 2 concentrations at the surface and midtroposphere (Keeling et al 1995;Jones et al 2001;Nevison et al 2008;Jiang et al 2010;Jiang et al 2012).…”
Section: Introductionmentioning
confidence: 99%